The sharing economy (New York, 2015)
"By unlocking the sharing economy today, can companies transform today's threat into tomorrow's opportunity? What must incumbents and challengers do to position themselves ahead of disruption and to capitalize on new sources of revenue? Through consumer surveys, conversations with influencers, interviews with business executives and social listening, PwC's research presents a holistic view of what's unfolding across business and consumer landscapes."